Impact of adherence to local antibiotic prophylaxis guidelines on infection outcome after total hip or knee arthroplasty. Issue 4 (August 2016) - Chandrananth, J.; Rabinovich, A.; Karahalios, A.; Guy, S.; Tran, P.
Summary: Background: National guidelines exist regarding preoperative antibiotic treatment for the prevention of surgical site infection (SSI); however, there are no published studies showing rates of compliance with them. Aim: To establish compliance with national guidelines within our institution, and the impact of adherence, on SSI rate. Methods: This was a retrospective observational study of 1019 patients undergoing hip or knee arthroplasty. Procedures were conducted at three metropolitan hospitals in Melbourne, Australia, throughout a 2.5-year period. Antibiotic prophylaxis recommendations were taken from the Australian Therapeutic Guidelines. Findings: Of the procedures included, 61.3% adhered to prophylaxis guidelines, 38.7% did not. The total SSI rate was 2.7%; with an infection rate of 1.7% in those adherent to antibiotic guidelines, compared with a rate of 5.0% if non-adherent ( P  < 0.01). Overall, 98.4% of patients received a dedicated prophylactic antibiotic dose as per guidelines. Of the procedures, 1.7% lasted >4 h with re-dosing being poorly adhered to (23.5% of procedures). In patients weighing >80 kg (49.5% of surgeries), guideline-concordant dosing occurred in only 58.7% of cases. For patients >80 kg without guideline-concordant dosing, the SSI rate was 6.6% and the odds ratio of SSI was 3.89 (confidence interval: 1.17–7.84; P  = 0.01). Conclusion: Non-adherence to guidelines increased the risk of SSI in patients undergoing total knee and hip arthroplasty. Dosing adjustment recommendations of prophylaxis for patients weighing >80 kg was poorly adhered to, and these patients were subsequently at higher risk of infection.